Aggregation‐Induced Emission (AIE) Nanoparticles‐Assisted NIR‐II Fluorescence Imaging‐Guided Diagnosis and Surgery for Inflammatory Bowel Disease (IBD). Issue 24 (28th July 2021) - Fan, Xiaoxiao; Xia, Qiming; Zhang, Yiyin; Li, Yirun; Feng, Zhe; Zhou, Jing; Qi, Ji; Tang, Ben Zhong; Qian, Jun; Lin, Hui
Abstract: The incidence of inflammatory bowel diseases (IBD), including Crohn's diseases and ulcerative colitis, is increasing by time and showing a trend of younger age. Precise diagnosis and effective treatments for IBD have attracted growing attention in recent years. However, diagnosing and locating inflammatory lesions remain a great challenge for IBD. In this study, assisted by a kind of aggregation‐induced emission (AIE) nanoprobes (BPN‐BBTD nanoparticles [NPs]), the second near‐infrared (NIR‐II) fluorescence imaging is first utilized to accurately trace inflammatory lesions, monitor inflammation severity and detect the response to the drug intervention in IBD mouse models. Through the advantages of high signal‐to‐background ratio (SBR) and sharp spatial resolution of bio‐imaging in NIR‐II region, the NIR‐II fluorescence imaging‐guided surgery can help to achieve a complete resection of severe inflammatory bowls and a secure surgical anastomosis. In addition, with the help of NIR‐II fluorescence wide‐field microscopy, the distribution of BPN‐BBTD NPs can be directly detected in tissue level and found to be mainly accumulated in mucosa and submucosa layers. This study highlights that AIE NPs‐assisted NIR‐II fluorescence imaging hold a great potential value for future diagnosis and imaging‐guided surgery in IBD. Abstract : Herein, assisted by a kind of excellent AIE fluoroprobe (BPN‐BBTD), utilize NIR‐II fluorescence imaging is utilized to accurately diagnose IBD and detect the response to the drug for the first time. An NIR‐II fluorescence imaging‐guided surgery for IBD is also initially explored, and an NIR‐II fluorescence wide‐field microscope is used to decipher the distribution of NPs in the diseased intestinal wall.